2017
DOI: 10.1159/000473889
|View full text |Cite
|
Sign up to set email alerts
|

Association Between <b><i>IFN-γ</i></b> Gene Polymorphisms and IgA Nephropathy in a Chinese Han Population

Abstract: Background/Aims: IFN-γ was reported to be involved in the development and progression of Immunoglobulin A nephropathy (IgAN), however, few studies have investigated the association between IFN-γ polymorphisms and IgAN. Therefore, we performed a case-control study to assess the association between IFN-γ polymorphisms and the risk of IgAN. Methods: Sequenom MassARRAY was used to genotype two SNPs (rs1861494 and rs2430561) in 351 patients with IgAN and 310 healthy controls. Associations were evaluated as odd rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Today, it is believed that atherosclerosis involves a maladaptive inflammatory response [25]. Several inflammatory cytokines take part in the development and progression of IgAN [26, 27]. Further research is necessary to clarify the precise roles of cytokines in the pathogenesis of intimal fibrosis in patients with IgAN.…”
Section: Discussionmentioning
confidence: 99%
“…Today, it is believed that atherosclerosis involves a maladaptive inflammatory response [25]. Several inflammatory cytokines take part in the development and progression of IgAN [26, 27]. Further research is necessary to clarify the precise roles of cytokines in the pathogenesis of intimal fibrosis in patients with IgAN.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact pathogenesis remains unknown. Genome-wide association studies have reported that multiple gene polymorphisms are correlated with the susceptibility to IgAN [4-9], including HLA-DQB1/DRB1, CFHR1, CFHR3, and HORMAD2 gene variants; our former studies also showed that IL-10 [10] and IFN-γ [11] polymorphisms were associated with the development of IgAN. These findings indicate that genetic factors are associated with the development and progression of IgAN.…”
Section: Introductionmentioning
confidence: 68%
“…The study included 351 patients with IgAN (229 males and 122 females, mean age of 32 ± 11.9 years) and 310 age- and sex-matched healthy controls (186 males and 124 females, mean age of 35 ± 12.6 years), details as shown in our previous studies [19-21]. There were no statistically significant differences between the two groups in terms of age and sex ( P ﹥0.05).…”
Section: Resultsmentioning
confidence: 93%